Common Bile Duct Polyp—Rare But Not So Rare Cause Of Obstructive Jaundice - Kabrawala, Mayank; Desai, Pankaj; Mehta, Rajiv; Nandwani, Subhash; Arora, Priya; Patel, Chintan; Bhatt, Keyur; Mangukiya, Dhaval; Parekh, Krishna (Journal of Digestive Endoscopy, 2020)
Polyps are usually found in gastrointestinal tract as their primary site of occurrence. In contrast, polyps in common bile duct (CBD) are uncommon. Biliary polyps can manifest as obstructive jaundice, which is the usually a presentation of common bile duct stone or malignant tumor of bile duct and pancreas. In this case series, we present five patients who had clinical manifestations of obstructive jaundice. However, systematic diagnostic approach in these patients revealed presence of polyps in distal CBD. We have focused on diagnostic challenges encountered during the investigation of CBD polyps.
Keywords: common bile duct polyps; obstructive jaundice; ERCP; sphincterotomy